LICHENS AND LICHENICOLOUS FUNGI NEW FOR THE PASVIK RESERVE (MURMANSK REGION) - Guennady Urbanavichus; Margarita Fadeeva (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2015)
Information on 39 species of lichens and lichenicolous fungi new for the Pasvik Reserve is provided. 23 of them are new for the biogeographic province Lapponia petsamoënsis.